Spanish adaptation and validation of the Dula Dangerous Driving Index (DDDI) - Sánchez López, María Teresa; Fernández-Berrocal, Pablo; Tagliabue, Mariaelena; Megías-Robles, Alberto (Wiley, 2024)
The Dula Dangerous Driving Index (DDDI) is a widely used questionnaire that measures the tendency to drive dangerously on the road through three different types of behaviors: aggressive driving, risky driving, and experiencing negative emotions while driving. This study aimed to develop a Spanish version of the DDDI and verify the reliability and validity of this questionnaire in the Spanish population. A community sample of 2174 Spanish participants (51.1% male; age range: 18–79 years) completed the 28-item Spanish version of the DDDI. Confirmatory factor analysis revealed that a three-factor model fitted adequately to the data. Analysis of internal consistency, test–retest reliability, and convergent validity showed that the Spanish adaptation of the DDDI had good psychometric properties and retains the theoretical consistency of the original scale. Gender and age differences were observed. The Spanish version of the DDDI can be considered a good instrument for assessing dangerous driving behavior, thus contributing to the cross-cultural study of these types of behaviors and the possible development of intervention programs aimed at reducing road traffic accidents.
Keywords: Tests psicológicos; Seguridad vial; Accidentes de tráfico; Emociones; Dangerous driving; DDDI; Reliability; Risky driving; Spanish adaptation; Validity